Too modest to lead: How men’s and women’s self-presentational strategies affect gender biases in manager selection - Torun Lindholm Öjmyr; Anna Blomkvist; Sebastian Cancino-Montecinos (Stockholm University, 2020)
This study examined how men's and women's self-presentational strategies in a professional context may contribute to a gender gap in career advancement. In a 3-step procedure, men and women first selected the questions they preferred to be asked during an employment interview for a highly qualified manager position. A naive sample of men and women then provided answers to these questions, and finally, a new naive sample of partticipants read these responses and evaluated applicants' suitability for the job. The uploaded files include metadata, and raw data for Step 1 and Step 3. Step 2 data, applicants' responses to the questions, are in Swedish and can be provided upon request.
Keywords: 170105 Gender Psychology; Personality, Social and Criminal Psychology; 170113 Social and Community Psychology; Organizational Behavioral Psychology; Psychology; Psykologi